Effect of bingo game instructional strategy on pupils’ achievement in mathematics in public primary schools in Oyo State, Nigeria (2021)
This study determined the effect of Bingo game instructional strategy on Pupils’ mathematics Achievements of public primary schools in Oyo state, Nigeria. One hundred and twelve public primary school grade 3 pupils participated in the study. This study adopted the pretest-posttest control group quasi-experimental design with a 2x3 factorial matrix. The study deployed Bingo strategy as different patterns that were designed to create fun and variety in teaching mathematics. The pretest was administered before the teaching using Bingo strategy, while posttest was administered immediately after the treatment (Bingo strategy). The control group were left with conventional teaching without any manipulation. Simple random sampling was used to select four primary schools from two local government area in Oyo State, Nigeria. Two constructed standardized and validated instruments by the researchers were used for the study: Pupils mathematics Achievement Test (r = 0.81) and Quantitative Ability Test (r = 0.69). The treatment lasted four weeks. The data were analyzed using Analysis of covariance at 0.05 level of significance. The result revealed that there was a significant main effect of Bingo on pupils achievement in mathematics (F(1, 110) = 3.327; partial η2 = 0.131).There was a significance main effect of quantitative ability (F(1, 110) = 0.603; partial η2 = 0.206) on pupils achievement in mathematics. The high quantitative ability pupils (56.904) benefited from the treatment package more than their counterpart (31.451). There was significant two-way interaction effect of Bingo game and quantitative ability of the participants (F(2, 106) = 1.543; partial η2 = 0.214) in favour of high quantitative ability pupils from Bingo game instructional strategy. The participants in Bingo game (14.07) had a higher mean value than their counterparts in the control (6.61). Bingo game instructional strategy improved pupils’ achievement in mathematics. Primary school mathematics teachers should try to adopt this strategy in their teaching delivery.